Farkas-type results for nonconvex systems involving composite functions with applications - Nguyễn, Định (Trường Đại học Đà Lạt, 2012)
A new kind of closednesa conditions (CC) is introduced. Several Farkastype results and their characterizations for nonconvex systems involving DC and composite functions are established under/via this condition. As applications, the results are applied to get optimality conditions, duality results for classes of DC/convex problems. Mathematics Subject Classification. Primary: 90C48, 90C46; Secondary: 49N15, 90C25.